De las mediaciones a los medios: la vida material de la espiritualidad contemporánea = From mediations to the media : the material life of contemporary spirituality - Viotti, Nicolas (Ciencias sociales y religión, 2018)
The emergence of a spiritual current, focused on practices identified with the New Age and with charismatic contemporary Christianity, is usually considered as a mode of internalization and radical subjectivation. In its more abstract versions, this perspective of analysis usually makes invisible the social, sacred and material mediations that articulate the production of subjectivity. Based on the analysis of some experiences of renewed Catholicism and alternative spiritual practices among educated sectors of Buenos Aires, this paper wants to show two things. First, it wants to depicts the centrality of objects, produced by cultural industry or even those that are out of it's circuit, as constitutive dimension of a relational and situated approach to religion. Secondly, the work also aims to reflect on the possibility of understanding material links as part of a specific and differential cosmological configuration of subjectivity production and its consequences in urban religious contemporary diversity.